THE INFLUENCE OF POWER POINT PRESENTATION TO IMPROVE STUDENTS’ READING SKILL OF SENIOR HIGH SCHOOL - Teacher, Margareth; Sirait, Andrian Petrus; Siahaan, Oloan Petrus; Harianja, Dapot (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This research was made to find out the influence of power point presentation in improving students’ reading skill. Beside that, this research has aim to find out the factors that influences the students’ reading skills improvement of narrative text. The researchers used classroom action research as the method of this research. The researchers also used test as an instrument by reading text in the power point presentation. From the result of the research, it shows that the students’ scores in reading text increasing. There is a major that influenced their improvement, which is the choice of material. The material should be new and relevant with the students’ imagination. Thus, they became interested in reading the text from the power point presentation.